Efficient measurement of power tower based on tilt photography with unmanned aerial vehicle and laser scanning. Issue 11 (16th August 2021) - Xia, Bin; Li, Zixin; Huang, Jianying; Zeng, Kaijun; Pang, Shiqiang
Abstract: A 3D laser scanning system can achieve the precision of millimetre level in deformation examination of a power line tower; however, it suffers from the high cost of equipment and difficult onsite installation. The Tilt Photography with Unmanned Aerial Vehicle (TP‐UAV) is a relatively lower cost system that offers a more convenient way of 3D measurement; however, with a trade‐off of lower measurement accuracy. In order to take advantage of both technologies and improve the measurement accuracy of the TP‐UAV system, in this research, a 3D laser scanning system is applied as a calibration means for the TP‐UAV to explore the possibility of rapid measurement of the deformation in transmission facilities. A data representation model is proposed for the calibration of the parameters of the TP‐UAV system to make use of the accuracy of the 3D laser scanning, and the systematic error of the TP‐UAV system can be corrected to improve the measurement accuracy by 35%.